Susan B. Anthony's women's right to suffrage speech - Orr, Tamra (21st century skills library. Front seat of history: famous speeches., 2021)
Briefly profiles Susan B. Anthony and highlights the impact of her speech on "Women's Right to Suffrage." Includes a glossary.